1995
DOI: 10.1099/00222615-42-5-353
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of human nasal mucosal explants with Neisseria meningitidis

Abstract: Summary. The interaction of Neisseria meningitidis with rhinopharyngeal epithelium was studied by experimental infection of explants of human nasal turbinate mucosa with two wild strains : a fully capsulate case isolate, and an epidemiologically related non-capsulate nasopharyngeal isolate. After incubation for 4 h, epithelial cells of infected explants changed conformation from tall columnar morphology towards cuboidal, and there was increased discharge of mucus globules from goblet cells. By 24 h there was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…More recently, biopsies of tissue have been used to study the importance of the mucus layer during the initial stages of adhesion of Mycobacterium to the human upper respiratory tract (29), and the interaction of C. jejuni with explanted intestinal mucosa (15). OCMs using adenoid or turbinate tissue have previously been used to investigate the behavior of N. meningitidis (34,35,47) but not for the identification of colonization factors. The advantage of using nasopharyngeal tissue is that it avoids the use of animal models which may lack human specific factors such as CD46 that are relevant for colonization (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, biopsies of tissue have been used to study the importance of the mucus layer during the initial stages of adhesion of Mycobacterium to the human upper respiratory tract (29), and the interaction of C. jejuni with explanted intestinal mucosa (15). OCMs using adenoid or turbinate tissue have previously been used to investigate the behavior of N. meningitidis (34,35,47) but not for the identification of colonization factors. The advantage of using nasopharyngeal tissue is that it avoids the use of animal models which may lack human specific factors such as CD46 that are relevant for colonization (20).…”
Section: Discussionmentioning
confidence: 99%
“…Upper airway OCMs consist of explants of human nasopharyngeal tissue and present bacteria with the physical epithelial barrier (consisting of polarized columnar cells joined by tight junctions) and subepithelial layer present in the upper airway. In addition, active cilia on the apical epithelial surface preserve mucociliary transport in OCMs, which express other mucosal innate immune factors (35). In OCMs, N. meningitidis must also utilize the same repertoire of carbon energy sources and other micronutrients that are present in the human nasopharynx (12).…”
mentioning
confidence: 99%
“…After adhesion, N. meningitidis can be found in the intracellular epithelial compartment (23,24,30). Several studies suggested that internalized capsulated bacteria are able to survive and even multiply within cells (12,14,21,29).…”
Section: Figmentioning
confidence: 99%
“…Monocytes are readily mobilized to sites of infection for local activation (8), and resident M are present in the nasopharynx and systemically, including at the blood-cerebrospinal fluid (CSF) interface (9). Meningococci were first observed within M in CSF from patients (3,18) and have been detected in M-like cells following experimental infection of explanted human rhinopharyngeal mucosa (30). Thus, M may be important during the initial and subsequent interactions between host and meningococci and during dissemination, as well as in the generation of acquired immunity.…”
mentioning
confidence: 99%